Editorial: social network analysis and economic geography$dpositional, evolutionary and multi-level approaches - Glückler, Johannes; Doreian, Patrick (Journal of economic geography, 2016)
Although social network analysis has gained popularity in economic geography over the last decade, most of these applications focused on analyzing the character
Gesehen am 19.06.2020